Oral Health Status of Pregnant Women attended the Mothers and Children Welfare Center (MCWC) in Bangladesh - Rahman, Md Mahafuzur; Hassan, Md Riasat; Islam, Md Ziaul; Ahmad, Mohammad Sayeed; Alam, Md Monirul; Islam, KM Mohidul (City Dental College Journal, 2013)
Aim: Oral health problem is one of the major health problems during pregnancy in both developing and developed countries. This cross-sectional study was carried out to assess the oral health status of the pregnant women attended some selected mothers and children welfare centers (MCWCs) in Bangladesh. Methods: Data was collected by face-to-face interview and clinical examination with the help of a structured questionnaire and check list. Results: Half (50.0%) of the pregnant women was of 15 to 20 years old and their mean age was 22.28±4.22 years. Thirty eight percent (38.2%) of the women had primary education and 78.4% did not visit any dentist. Majority (93.1%) used tooth brush before breakfast and most (84.4%) of them had no information about oral hygiene care. Regarding oral health status, 87.3% had caries affected teeth and 94.1% had gingivitis. Presence of gingivitis and calculus were higher among the elder women (21-35 years) than the younger group (15-20 years) which was 92.2% among the housewives. Gingivitis was significantly higher among the women in low income group (95.7%) than the other income groups (X2 = 5.80, p<0.05). Conclusion: The study findings recommended for provision of essential dental health services to the pregnant women for prevention and control of various dental health problems during pregnancy. DOI: http://dx.doi.org/10.3329/cdcj.v10i2.16312 City Dent. Coll. J Volume-10, Number-2, July-2013